Implementasi Dakwah Bil Hal Kader Ranting Muhammadiyah Klawuyuk Kota Sorong - Zainal, Nur Endang (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
This study discusses the Implementation of Dakwah Bil Hal Cadre Branch Muhammadiyah Klawuyuk Sorong City. This study aims to determine the implementation of da'wah bil hal and the constraints of the cadres of the Muhammadiyah branch of Klawuyuk, Sorong City. After the compiler carried out data analysis techniques, the results of the research found that the da'wah bil hal carried out by the cadres of the Muhammadiyah Klawuyuk branch consisted of several programs, the first religious program in this program was the construction of mosques, the construction of TPQ and recitation. The second program is social which consists of managing the bodies, and distributing basic food items. The last program is an economic program where this program takes place with the opening of the Ababil TPQ KH depot. Mas Mansyur and two business units leased out to the local community. The obstacles in the implementation of da'wah bil hal cadres of the Muhammadiyah branch of Klawuyuk, City of Sorong, namely the first factor comes from the management who is constrained by the distribution of time and division of tasks in coordinating activities with obligations in carrying out the work they are obliged to do. The second factor is the limited media, facilities and infrastructure in the implementation of da'wah bil hal.